Recognition of whole blood transfusion in civilian trauma resuscitation - Weijuan MA; Shaomin REN; Zhongsi YANG; Yanhua ZHANG (Zhongguo shuxue zazhi, 2024)
There has been a growing amount of evidence that a balanced blood component transfusion with roughly equal ratio of units of packed red blood cells, fresh frozen plasma, and platelets leads to better outcomes in massive transfusion resuscitation of trauma victims. Therefore, the great interest of massive transfusion protocol (MTP) with whole blood was aroused. Low titer group O whole blood (LTOWB) is implemented in routine use for civilian prehospital ambulance services in large trauma centers of most European and American countries nowadays. There is a growing body of evidence to date to support that early use of LTOWB in patients with life-threatening bleeding improve their survival. In view of the current situation of whole blood supply in our country, most trauma resuscitation guidelines still recommend balanced component transfusion for MTPs in the early stage of resuscitation. The research and application of LTOWB abroad will be introduced in this article.